2005
DOI: 10.1007/s00425-005-0105-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of DNA sequences controlling the expression of the rice OsCDPK2 gene

Abstract: Plant calcium-dependent protein kinases (CDPKs) are involved in calcium-mediated signal transduction pathways. Their expression is finely tuned in different tissues and in response to specific signals, but the mechanism of such a regulation is still largely unknown. OsCDPK2 gene expression is modulated in vivo during rice (Oryza sativa L.) flower development and is downregulated by white light in leaves. In order to identify OsCDPK2 regulatory sequences, we amplified and cloned both the 5' and 3'-flanking regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…The obtained results demonstrate that these two CDPKs differ in their temporal and special distribution to accomplish their diverse physiological role. Available data show that most CDPK isoforms are expressed constitutively and neither organ nor tissue specificity were observed (Morello et al 2006). However for some of them a unique, very restricted expression pattern and enzyme activity in different organs or tissues at different stages of growth and development were noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results demonstrate that these two CDPKs differ in their temporal and special distribution to accomplish their diverse physiological role. Available data show that most CDPK isoforms are expressed constitutively and neither organ nor tissue specificity were observed (Morello et al 2006). However for some of them a unique, very restricted expression pattern and enzyme activity in different organs or tissues at different stages of growth and development were noted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two main enzymes, Suc-phosphate synthase (SPS) and nitrate reductase (NR), are inactivated in the dark by CDPK phosphorylation on specific Ser residues (McMichael et al 1995;Douglas et al 1998). It might coordinate the supply of carbon skeletons and ammonia needed for starch synthesis or amino acids when photosynthesis is off (Cheng et al 2002;Morello et al 2006;Klimecka and Muszyńska 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that enhancer elements are generally present in the introns of the 5′ UTR region, suggesting that the introns located in the 5′ UTR region may play an important role in the regulation of gene expression by regulating mRNA stability, the efficiency of translation, or can directly impact transcriptional regulation (Maas et al, 1991;Gidekel et al, 1996;Bailey-Serres and Gallie, 1998;Plesse et al, 2001;Morello et al, 2002;Fiume et al, 2004;Wang et al, 2004;Gutiér-rez-Alcalá et al, 2005). In addition, plant intron sequences were reported to enhance functional gene expression in transgenic plants, and this intron-mediated enhancement (IME) of gene expression has been reported for several genes, indicating that the first 5′-leader intron is necessary for a high-level gene expression and can autonomously promote transcription (Mascarenhas et al, 1990;Vasil et al, 1990;Maas et al, 1991;Clancy et al, 1994;Rose and Beliakoff, 2000;Kim et al, 2004;Morello et al, 2002Morello et al, , 2006Gutiérrez-Alcalá et al, 2005;Kim et al, 2006;Sivamani and Qu, 2006). Thus, introns may influence and enhance gene expression by multiple mechanisms (Le Hir et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the increase in protein accumulation caused by introns exceeded that in mRNA accumulation, supporting the notion that plant introns also elevate translation (Mascarenhas et al 1990;Bourdon et al 2001;Clancy and Hannah 2002;Rose 2004). Interestingly, IME studies in dicot plants were usually performed in stably transformed plants (Fu et al 1995a, b;Chaubet-Gigot et al 2001;Rose 2002;2004) whereas most IME studies in monocot plants were carried out by transient expression assays in cultured cells (Callis et al 1987;Mascarenhas et al 1990;Rethmeier et al 1997;Bourdon et al 2001;Clancy and Hannah 2002;Morello et al 2006;Sivamani and Qu 2006) with few exceptions (Jeon et al 2000;Dugdale et al 2001;Bourdon et al 2004). Moreover, few studies simultaneously investigated the characteristics of IME in diVerent tissues of plants.…”
Section: Introductionmentioning
confidence: 88%